Multilevel surface nano- and microstructuring via sequential photoswelling of dichromated gelatin - Paszewski, Maciej (Langmuir : the ACS journal of surfaces and colloids, 2007)
Photoswelling of thin films of dichromated gelatin provides a basis for fabrication of multilevel surface reliefs via sequential UV illumination through different photomasks. The remarkable feature of this simple, benchtop technique is that by adjusting irradiation times, film thickness, or its hydration state the heights of the developed features can be varied from few nanometers to tens of microns. After UV exposure, the surface structures can be replicated faithfully into either soft or hard PDMS stamps